STATUS OF MULTIPLE OWNERSHIP LAND CERTIFICATES ACCORDING TO GOVERNMENT REGULATION OF LAND REGISTRATION - Seno, Anto; Wijaya, Arya (SYNTIFIC, 2023)
Background. Certificate as legality of ownership land, registering land rights is an important thing to ensure certainty for land rights holders and other parties who have an interest in the land. The research purposed to determine the status of multiple ownership land certificates according to government regulation of land registration. Research Method. This research is considered as a field research or case study. It uses used descriptive analysis method and the type of research is qualitative research. The data collection procedures of this study were observation, interviews, and documentation. The case study of Jakarta Religious Court Decision 619/Pdt.J/2023/PN.Jkt. Findings. There are 2 (two) ways to obtain a land title certificate systematic registration and sporandic registration is a registration activity that is carried out simultaneously in one place a certain region or region, or a village sub-district where the land is located. Conclusion. Certificate as legality of land ownership, registering land rights is an important thing to guarantee legal certainty and protection of land rights holders and other parties with interests in the land.